Optimizing high harmonic generation in hollow-core gas cell considering variation of gas density - KIM YONGSOO; Moon Byunghyuck; Kim, Chulki; Ju, Byeong-kwon; Lee, Ju Han; Jhon, Young Min (Elsevier BV, 2022)
We have developed a coherent and compact extreme-ultraviolet light source based on phase-matched high harmonic generation by using a hollow-core gas cell that can be easily aligned and maintain long stability. The gas cell consists of three bodies to minimize gas leakage and maintain stable vacuum. The photon flux was calculated considering the dependence of the gas number density and the pressure on the radii of the hollow core and the hole in the Al plates on both sides of the gas cell, which showed good coincidence with the experimental values. The photon flux is 2 x 10(10) photons s(-1) near 13.5 nm (91.5 eV) within 10 nm bandwidth. Also, the compact extreme-ultraviolet light source is found to operate stably for hours, which is suitable for practical applications such as metrology and inspection for extreme-ultraviolet mask, spectroscopy, holography, microscopy, etc.